Evaluation of Hearing Status in Various Type of Cerebral Palsy Children in a Tertiary Hospital - Biswas, Sanchita; Saha, Debashis; Rahman, Mizanur; Paul, Debatosh (Bangladesh Journal of Child Health, 2023)
Background: Cerebral palsy (CP) in children are frequently associated with sensorineural pathology. Objectives: To assess the severity of hearing impairment in children with CP and correlate the auditory impairment with different types of CP. Materials & Methods: This cross-sectional study was conducted in the Department of Pediatric neurology and Autolaryngiology- Head and Neck Surgery BSMMU, during March to September 2011. Diagnosed CP patients were included consecutively. After taking informed written consent, proper history and clinical examinations was done and severity of hearing loss was assessed. Results: Among the 50 children with CP, Tympanometry result revealed that negative middle ear pressure was present in 32% in spastic quadriplegia(SQ), 24% in spastic hemiplegia (SH), 16% in spastic diplegia (SD) and 24% in mixed type. Eustachian tube dysfunction was present in 62.5% in spastic hemiplegia. In TOAE result 52% were pass and 48% were referred and ABR were suggested. On the basis of result of TOAE, those were referred, initially they were encountered as hearing impairment in this study. Among them, in SQ were 18%, SH were 12% and mixed. Follow up auditory brain stem response revealed mild, moderate and severe sensorineural hearing loss were 8% in spastic quadriplegic type and the spastic diplegia and athetoid group were 2% only mild, Moderate sensorineural hearing were 2% in spastic hemiplegia group. Conclusion: Spastic Quadriplegic cerebral palsy patients had the maximum incidence of hearing impairment. Perinatal asphyxia and prematurity were the main risk factor of hearing impairment. BANGLADESH J CHILD HEALTH 2022; VOL 46 (1) : 19-22